Pengaruh Penyajian dan Aksesibilitas Laporan Realisasi Dana Desa Terhadap Akuntabilitas Pengelolaan Dana Desa (Studi Kasus Desa Pulosari, Kecamatan Bareng, Kabupaten Jombang) - Siti Mureni (JFAS : Journal of Finance and Accounting Studies, 2020)
This type of research is quantitative research. Data collection technique used is questionnaires. The purpose of the study was to determine the effect of the presentation and accessibility of the report on the realization of village funds on the accountability of village fund management in Pulosari, Bareng , Jombang. The data analysis technique used is multiple linear regression analysis. The results of this study indicate a positive and significant influence from the presentation and accessibility of the realization report on the accountability of village fund management. This shows that if the Pulosari government presents a report on the realization of village funds well and the accessibility of reports is easy to obtain, it will increase the accountability of the Pulosari government. The Accountability is needed as an illustration that the organization of the organization is going well.